Nostalgiczny uśmiech. Autobiograficzny film Mateja Bobrika Self(less) Portrait - Mąka-Malatyńska, Katarzyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
The auto-documentary has a very short tradition in Polish cinema. The first films of this type were produced in Poland in the 1990s, when students of the National Film School in Łódź started making short films about themselves. In my essay, I focus on one such film, Self(less) Portrait, made by Matej Bobrik in 2012. The film tells the story of two young people: she is from Japan; he is from Slovakia and is the film’s director. They both studied film directing at the NFS in Łódź, and now live together in Warsaw. In the film, Bobrik shows the difficult relationship that exists between the two characters and members of their families, who live far away. It is a story about closeness, endearment, loneliness and death. In Self(less) Portrait, seriousness, sadness and nostalgia meet with humour and the grotesque. The article concentrates on the construction of the film, and the use of symbolism and humor in it. This is an exceptional film in contemporary Polish cinema because Bobrik does not engage in self-therapy – he does not accuse or talk about traumatic experiences, as Marcin Koszałka or Paweł Jóźwiak-Rodan do in their auto-documentaries.

Dokument autobiograficzny ma bardzo krótką tradycję w historii polskiego kina. Pierwsze filmy tego typu powstały w latach dziewięćdziesiątych, gdy studenci Państwowej Wyższej Szkoły Filmowej w Łodzi zaczęli robić filmy o sobie samych. W moim eseju koncentruję się na jednym z takich filmów, Self(less) Portrait Mateja Bobrika z 2012 roku. Film opowiada historię dwojga młodych ludzi: ona jest z Japonii; on pochodzi ze Słowacji i jest reżyserem filmu. Oboje studiowali reżyserię w PWSFTviT w Łodzi, a teraz mieszkają razem w Warszawie. W swoim filmie Bobrik pokazuje trudną relację między bohaterami i członkami ich rodzin, którzy żyją daleko. Jest to historia o bliskości, czułości, samotności i śmierci. W filmie Self(less) Portrait powaga, smutek i nostalgia spotykają się z humorem i groteską. Artykuł koncentruje się na konstrukcji filmu i sposobach wykorzystania symboliki i humoru. To wyjątkowy film w historii współczesnego kina polskiego, ponieważ celem Bobrika nie jest autoterapia – nie wysuwa on oskarżeń ani nie opowiada o traumatycznych przeżyciach, jak czynią to Marcin Koszałka lub Paweł Jóźwiak-Rodan w swoich dokumentach autobiograficznych.
A Nostalgic Smile. Autobiography in the Documentary Film Etude Self(less) Portrait by Matej Bobrik
Katarzyna Mąka-Malatyńska, Katedra Filmu, Telewizji i Nowych Mediów UAM, Nostalgiczny uśmiech. Autobiografizm w dokumentalnej etiudzie Self(less) Portrait Mateja Bobrika, A Nostalgic Smile. Autobiography in the Documentary Film Etude Self(less) Portrait by Matej Bobrik, „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20, ISSN 1731-450X, język: polski
Keywords: auto-documentaries; short film; school film; Matej Bobrik; Self(less) Portrait; dokument autobiograficzny; film krótkometrażowy; szkoła filmowa